2019
DOI: 10.1111/jph.12846
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic resistance in tomato against broomrape (Phelipanche aegyptiaca)

Abstract: Rhizosphere dwelling bacteria can increase plant resistance to biotic and abiotic stresses, and they promote plant growth through various mechanisms. In this study, three bioassays were conducted including the following: (a) screening for effective bacterial isolates in the suppression of broomrape, (b) evaluating induced systemic resistance against broomrape and (c) comparing the selected bacterium isolate with plant chemical inducers. Fifteen plant growth‐promoting rhizobacteria (PGPR) were examined to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, induced systemic resistance (ISR), potentiated by numerous strains of nonpathogenic microorganisms such as plant growth-promoting rhizobacteria (PGPR), is another route to boost the broad-spectrum immunity in plants [93,99,100]. Many studies have shown the efficacy of PGPR to induce ISR such as in tomato to defend Phelipanche aegyptiaca [101] and Pseudomonas syringae [102]; cotton against Macrophomina phaseolina (Tassi) [71]; tobacco to resist Tobacco mosaic virus [103]; mung bean to protect against Macrophomina phaseolina [104]; rice against Xanthomonas campestris [105]; and tomato to defend Ralstonia solanacearum [106]. erefore, research on the induction of disease resistance using biotic and abiotic inducers is desirable and can be regarded as one of the effective approaches to FBG management.…”
Section: Biotic and Abiotic Stresses Induced Host Defensementioning
confidence: 99%
“…Moreover, induced systemic resistance (ISR), potentiated by numerous strains of nonpathogenic microorganisms such as plant growth-promoting rhizobacteria (PGPR), is another route to boost the broad-spectrum immunity in plants [93,99,100]. Many studies have shown the efficacy of PGPR to induce ISR such as in tomato to defend Phelipanche aegyptiaca [101] and Pseudomonas syringae [102]; cotton against Macrophomina phaseolina (Tassi) [71]; tobacco to resist Tobacco mosaic virus [103]; mung bean to protect against Macrophomina phaseolina [104]; rice against Xanthomonas campestris [105]; and tomato to defend Ralstonia solanacearum [106]. erefore, research on the induction of disease resistance using biotic and abiotic inducers is desirable and can be regarded as one of the effective approaches to FBG management.…”
Section: Biotic and Abiotic Stresses Induced Host Defensementioning
confidence: 99%